2015
DOI: 10.1016/j.psep.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Rotating biological contactors for wastewater treatment – A review

Abstract: Rotating biological contactors (RBCs) for wastewater treatment began in the 1970's. Removal of organic matter has been targeted within organic loading rates of up to 120 g.m -2 d -1 with an optimum at around 15 g.m -2 d -1 for combined BOD and ammonia removal. Full nitrification is achievable under appropriate process conditions with oxidation rates of up to 6 g.m -2 d -1 reported for municipal wastewater. The RBC process has been adapted for denitrification with reported removal rates of up to 14 g.m -2 d -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(58 citation statements)
references
References 128 publications
(185 reference statements)
1
52
0
5
Order By: Relevance
“…The RBC system is an alternative to the activated sludge process that has been called a disc, surface, media and biofilm reactor [100]. RBCs consist of parallel packs of rotating discs with attached microorganisms on their surfaces in the form of biofilms.…”
Section: Rotating Biological Contactor (Rbc)mentioning
confidence: 99%
“…The RBC system is an alternative to the activated sludge process that has been called a disc, surface, media and biofilm reactor [100]. RBCs consist of parallel packs of rotating discs with attached microorganisms on their surfaces in the form of biofilms.…”
Section: Rotating Biological Contactor (Rbc)mentioning
confidence: 99%
“…Rotating biological contactors (RBCs) are cost-effective and flexible attached growth bioreactors, which are widely used to treat various wastewater including domestic wastewater [14][15][16][17], dye wastewater [18], and landfill leachate [19]. The RBCs are fascinating options to decentralized wastewater treatment due to high specific surface area, high biomass content, low footprint, and easy operation [20]. Even though RBCs are mostly reliable, they still have some shortcomings in terms of costs and stable nitrogen removal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Jia Yanping [9] study found that higher COD load not only increases the cost of adding carbon source, but also inhibit the autotrophic nitrification bacteria growth, and reduce the removal efficiency of NH4 + -N. When the inlet velocity is constant, the reflux ratio is determined by the circulation speed. And the change of the circulation rate has great influence on the dissolved oxygen in the wastewater and the thickness and shear stress of the liquid phase layer when the wastewater flows through the biological membrane, which further affects the operation efficiency of the reactor [10][11] . If continue to increase the return ratio, not only increased the thickness and the influence of mass transfer of liquid layer, the hydraulic shear stress increases greatly, resulting in the biofilm is large and scattered off, directly influence the operation efficiency, and high reflux ratio to consume more capacity, mechanical damage probability will increase [11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…And the change of the circulation rate has great influence on the dissolved oxygen in the wastewater and the thickness and shear stress of the liquid phase layer when the wastewater flows through the biological membrane, which further affects the operation efficiency of the reactor [10][11] . If continue to increase the return ratio, not only increased the thickness and the influence of mass transfer of liquid layer, the hydraulic shear stress increases greatly, resulting in the biofilm is large and scattered off, directly influence the operation efficiency, and high reflux ratio to consume more capacity, mechanical damage probability will increase [11][12] . Based on the existing biological treatment process, designed a set of A 2 /O 2 technology of biological membrane reactor to rural sewage treatment in Southern China area, which is characterized by small footprint, low energy consumption, pollutant removal efficiency, high nitrogen removal function, simple management, the effluent can meet the discharge standard.…”
Section: Introductionmentioning
confidence: 99%